Real Time Public Transportation Navigator System in Jakarta by Using Greedy Best First Search Algorithm - Elizabeth, Monica; Gani, Billy; Safitri, Marreta Anggun; Dewi, Lusiana Citra; Meiliana, Meiliana (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
According to Castrol’s Magnetec Stop-Start index 2015, Jakarta was determined as the most traffic jam city in the world. This condition is getting worse in 2016 with significant increase of private vehicle number in Jakarta. In order to tackle this problem, current Jakarta’s governor stated that the only working theory to dissolve the congestion in Jakarta is to make people willing to commute using public transportation. However, there is no integrated system to facilitate and navigate the usage of public transportation in Jakarta. In order to help the government to encourage people to use the public transportation, an integrated public transportation system is developed. On the first development phase, this system will integrate two main public transportations in Jakarta: train KRL and bus TransJa-karta. Greedy best first search algorithm is implemented to calculate fastest route information. Routes, direction, current location and others real time information is provided by using Google Map service. Some alternative routes based on cost, distance and time will be shown to facilitate user preferable. The system is developed for three main platforms: website, android, and iOS to cover user’s usage diversity in Jakarta. Based on survey conducted on the last phase on development cycle, 90 percent of respondent says that the navigation information is accurate.